ISLAM LIBERAL BUDHY MUNAWAR RACHMAN (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
Islamic thought in Indonesia will never end, Islam is always interesting to observe, one of which is about the birth of liberal Islamic thought in the 1970s. This started when Cak Nur gave a speech at the Eid al-Fitr gathering organized by HMI, PII, GPI and Persami. In his speech he said that Islamic thought is currently in a state of confusion, because there are many Islamic parties who want to revive an Islamic state. Therefore, Cak Nur proposed a controversial cargon, namely